2019
DOI: 10.3390/f10010033
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Estimation and Antimicrobial Activity of Culturable Endophytic Fungi from Litsea cubeba (Lour.) Pers. in China

Abstract: Endophytes are important components of forest ecosystems, and have potential use in the development of medical drugs and the conservation of wild medicinal plants. This study aimed to examine the diversity and antimicrobial activities of endophytic fungi from a medicinal plant, Litsea cubeba (Lour.) Pers. The results showed that a total of 970 isolates were obtained from root, stem, leaf, and fruit segments of L. cubeba. All the fungal endophytes belonged to the phylum Ascomycota and could be classified into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Some genera of endophytes reported in this study are commonly found in the leaves and branches of other hosts: species of Diaporthe, Fusarium, Lasiodiplodia, and Trichoderma are found in branches of Theobroma cacao in Brazil (Rubini et al 2005); Alternaria and Epicoccum have been reported from the branches of Prunus cerasus in the Czech Republic (Hortová & Novotný 2011); Alternaria, Diaporthe, and Fusarium spp. have been reported from branches of Vitex rotundifolia in Taiwan (Yeh & Kirschner 2019); and Diaporthe and Phoma species were registered from the branches of Litsea cubeba in China (Wu et al 2019). Endophytes from leaflets were mainly found isolates of Diaporthe and Alternaria from Hevea brasiliensis in Brazil (Vaz et al 2018) and Peru (Gazis & Chaverri 2010); Alternaria, Diaporthe, and Curvularia from leaflets of Prosopis juliflora in India (Srivastava & Anandrao 2015); Byssochlamys, Curvularia, and Alternaria from leaves of Euphorbia prostate, Calotropis procera, and Catharanthus roseus in Sudan (Khiralla et al 2016); and Sarocladium from leaves of Myracrodruon urundeuva in Brazil (Pádua et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some genera of endophytes reported in this study are commonly found in the leaves and branches of other hosts: species of Diaporthe, Fusarium, Lasiodiplodia, and Trichoderma are found in branches of Theobroma cacao in Brazil (Rubini et al 2005); Alternaria and Epicoccum have been reported from the branches of Prunus cerasus in the Czech Republic (Hortová & Novotný 2011); Alternaria, Diaporthe, and Fusarium spp. have been reported from branches of Vitex rotundifolia in Taiwan (Yeh & Kirschner 2019); and Diaporthe and Phoma species were registered from the branches of Litsea cubeba in China (Wu et al 2019). Endophytes from leaflets were mainly found isolates of Diaporthe and Alternaria from Hevea brasiliensis in Brazil (Vaz et al 2018) and Peru (Gazis & Chaverri 2010); Alternaria, Diaporthe, and Curvularia from leaflets of Prosopis juliflora in India (Srivastava & Anandrao 2015); Byssochlamys, Curvularia, and Alternaria from leaves of Euphorbia prostate, Calotropis procera, and Catharanthus roseus in Sudan (Khiralla et al 2016); and Sarocladium from leaves of Myracrodruon urundeuva in Brazil (Pádua et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Colletotrichum boninense is the dominant species. For the antimicrobial activities, 17 isolates could inhibit the growth of plant pathogenic fungi, while the extracts of 6endophytes show antimicrobial activity to all the tested pathogenic fungi [18].…”
Section: Theme 2: Above-and Below-ground Forest Biodiversitymentioning
confidence: 97%
“…In Chinese herbal medicines, diverse fungal endophyte communities isolated from the roots of Paris polyphylla have traditionally been employed. Similarly, the colletotric acid (C 28 H 28 O 10 ) antimicrobial substance produced by the fungal endophyte Colletotrichum gloesporoides from the Chinese medicinal plant Artemisis mongolica has potentially displayed antimicrobial properties [ 46 ].…”
Section: Pharmacological Effects Of Bioactive Compounds Of Fungal mentioning
confidence: 99%